Combined spinal-epidural technique: Single-space vs double distant space technique - Slavković Zoran; Stamenković Dušica M.; Gerić Veselin; Veljović Milić; Ivanović Nebojša; Todorović Slobodan; Marić Predrag; Karanikolas Menelaos (Vojnosanitetski Pregled)
Background/Aim. Several combined spinal-epidural (CSE) anesthesia techniques have been described. This study was designed to compare the single space (“needle-throughneedle”) technique (SST) and the double distant space technique (DDS) with regards to the time needed for the procedure, patient discomfort during the procedure and patient's preference technique. Methods. This prospective, randomized single-blind study included 156 patients undergoing colorectal surgery under general anesthesia and CSE. All neuraxial blocks were performed before general anesthesia induction. DDS group of patients had thoracic epidural catheter placed at T6-7 or T7-8, followed by subarachnoid injection at the L2-3 interspace. The SST group of patients had a single injection using the needle-through-needle technique (Espocan® needle) at L2-3. The epidural catheter was used for postoperative analgesia for 72 hours. Body habitus, spinal anatomy and spinal landmarks were assessed preoperatively. The number of epidural and spinal punctures, the feeling that the dura is perforated (dural perforation click) and the time needed to perform CSE were also recorded. Complications during epidural catheter placement and perioperative and postoperative epidural catheter function and patient preference for the anesthetic procedure were recorded. Results. Epidural and subarachnoid spaces were successfully identified in all the patients. Duration of CSE procedure, the number of spinal punctures, dural click feeling and the effects of test dose did not differ between the groups. The patients in both groups (90% of DDS and 87% of SST) would choose CSE as preferred method in the future. The CSE procedure was painful for 16% of DDS vs 20% of SST patients. A significant correlation between time needed for CSE technique performance and body habitus (r = 0.338, p < 0.01), spinal landmarks (r = 0.452, p < 0.001) and anatomy (r = 0.265, p < 0.05) was found in the SST group. There was no correlation between the number of epidural/spinal punctures and epidural bacteriological findings. There was no correlation between the patients’ choice of the CSE technique and the number of spinal punctures, duration of CSE procedure and epidural catheter stay. Conclusion. The two CSE techniques did not differ with regards to the procedure time and patient's preference. Procedure time correlated with body habitus, spinal landmarks and the anatomy in the SST group.